Changing new content, operating methods of industrial Unions in the current period - Dương Văn Sao (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
In organizing activities, the content of activities is the most important, it is reflected in specific programs and plans of activities. The content of trade union activities regulates the organizational apparatus and operation method of the trade union. Although the trade union’s operation method depends on the operation content and organizational structure of the trade union, the trade union’s method of operation also plays an increasingly important role in the activities of the trade union, it directly affects the trade union’s activities in terms of the quality and performance. On the basis of content analysis, limitations on the content and activities of industrial unions, the article proposes a number of solutions to innovate the content and operation methods of trade unions in the current period.